Repeated low-dose computed tomography in current and former smokers for quantification of emphysema - McGregor, Alexander; Roberts, Heidi C.; Dong, Zhi; Menezes, Ravi; Kauczor, Hans-Ulrich; Weinheimer, Oliver; Heußel, Claus Peter (Journal of computer assisted tomography, 2010)
Objective: - To quantify different emphysema evolution in current and former smokers. - Methods: - We retrospectively analyzed low-dose computed tomography scans from a lung cancer screening study of 59 current and 75 former smokers. The quantitative emphysema analysis was performed using a home-built software (YACTA version 0.9), yielding the parameters lung volume, emphysema volume (EV), emphysema index (EI), mean lung density, and 15th percentile. - Results: - The baseline EV and EI were significantly different (median EVformer =422 mL vs EVcurrent =249 mL, P = 0.0003; and median EIformer =7.6 % vs EIcurrent =4.1 %, P = 0.0001, respectively). On the annual repeat scan, the median EI and EV for former smokers had decreased significantly (ΔEIformer = −0.257%, P = 0.004; and ΔEVcurrent = −0.203 mL, P = 0.020), whereas there was no emphysema change in current smokers. - Conclusions: - We were able to demonstrate different emphysema evolution in current versus former smokers; emphysema parameters decreased in the former smokers and remained stable in current smokers.